What do we know about using drama techniques to promote restorative practices? - Hutchby, Claire (2015)
Using a qualitative interpretive approach, I will be investigating what we know about drama techniques and how they can be used to promote restorative practices. I will be arguing that there is evidence, from the arenas of restorative practices, drama-therapy and the criminal justice sector, to suggest that drama techniques have the potential to promote the underlying principles of the restorative approach. My research objectives seek to highlight and expose the areas of most interest to the academic community in regards to my overarching question. I will be highlighting the position of both drama and restorative practices within the current educational landscape and linking these findings into my implications. Furthermore, a key finding, and basis for academic argument throughout, is that drama’s ability to promote restorative practices is in need of further investigation. Key Words: Restorative practices, Drama techniques, Imagined experience